2021
DOI: 10.3390/nu13082626
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Lifestyle Risk Factors and Depression in Korean Adults: A Moderating Effect of Overall Nutritional Adequacy

Abstract: Background: Little is known regarding the role of nutrition in determining the associations between lifestyle risk factors and depression. Objectives: This study examined whether or not nutritional adequacy modulates the relationship between depression and lifestyle risk factors in Korean adults aged 18-65 years (n = 7446). Methods: Data were obtained from the 2016 and 2018 Korea National Health and Examination Survey. Depression, smoking, at-risk alcohol consumption, physical inactivity, sleep deprivation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Numerous research findings using these data have been published, and research on depression is currently being undertaken. Using the KNHANES V-VII (2010-2018) data, it has been reported that depression is associated with low intake of fruits and vegetables [82], low consumption of curry rice [83], seaweed and mushroom [84], sugar-sweetened beverages consumption (≥ 1/day) [85], short sleep (≤ 6 h) [86], increased work-related physical activity, decreased recreational physical activity [84,87], poor dietary habits [88,89], gender difference, night eating, and nutritional adequacy [90] in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous research findings using these data have been published, and research on depression is currently being undertaken. Using the KNHANES V-VII (2010-2018) data, it has been reported that depression is associated with low intake of fruits and vegetables [82], low consumption of curry rice [83], seaweed and mushroom [84], sugar-sweetened beverages consumption (≥ 1/day) [85], short sleep (≤ 6 h) [86], increased work-related physical activity, decreased recreational physical activity [84,87], poor dietary habits [88,89], gender difference, night eating, and nutritional adequacy [90] in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disturbances such as insomnia and hypersomnia are the most prominent symptoms among depressed patients, with a stronger prevalence in females [37]. Third, there are other potential factors for gender differences in these relationships, including socio-economic status [20], social factors [20], nutritional adequacy [38], and others [39]. Lastly, biological factors such as cholesterol, cytokines, and appetite regulating hormones are also involved in the gender differences of the relationships between behavioral risk factors and depression [34], which remain to be further investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep quality in relation to MDD risk should be further investigated. Fourth, the relationship between behavioral risk factors and depression may be mediated by other factors, such as, socio-economic and social factors, nutritional status and others [35][36][37][38][39][40], which needs to be further addressed in a future study. Lastly, although the accuracy of the PHQ-9 score for screening MDD was previously tested and validated in Korean elderly populations [24], it is a subjective screening test and not cover all depression criteria.…”
Section: Discussionmentioning
confidence: 99%
“…First, the cross-sectional nature of the study limits any determination about causality regarding the association between sarcopenia and depressive symptoms. Second, the relationship between sarcopenia and depressive symptoms may be influenced by other factors, such as nutritional status [ 42 ], socioeconomic status [ 31 ], and existing health conditions [ 43 ], which needs to be further addressed in a future study. Third, a reverse relationship between sarcopenia and depressive symptoms may also exist.…”
Section: Discussionmentioning
confidence: 99%